Gestão ambiental: um novo desafio para os profissionais de recursos humanos? - Freitas, Wesley Ricardo Souza; Jabbour, Charbel José Chiappetta; Gomes, Angelica Fabiana [UNESP] (My University, 2011)
Current research analyzes the importance of human resources managers in organizational sustainability through the ack-nowledgement of the external variables and innovatory practices, such as environment management. In fact, the latter is a challenge for organizations and consequently for the human resources’ area. Investigation comprised a revision of the literature: theoretical and empirical articles that deal with the role of human resources’ mana-gement and on the environmental issue which is daily in the news. The essay is divided into three parts: the first section emphasizes the role of human resources’ managers; empirical evidences of the activities of HR managers in international contexts are dealt with in the second part; the third section deals with the environmental ma-nagement issue as a new challenge for HR managers. HR managers should acknowledge and incorporate in human resources practice the environmental dimension from the stages of recruitment, selec-tion and training. If people with attitudes and competences in the environment are rewarded, they will contribute towards an effective environmental management and, consequently, improvements in organizational results will materialize.

Este trabalho tem como objetivo fazer uma reflexão sobre a importância do papel dos gestores de recursos humanos para a sustentabilidade organizacional, a partir do reconhecimento das variáveis externas e da incorporação de práticas inovadoras, como a gestão ambiental, que é um novo desafio que se apresenta para as or-ganizações e, consequentemente, para a área de recursos humanos. Para a realização da pesquisa foram utilizados artigos teóricos e/ou empíricos que abordaram o papel dos gestores de recursos huma-nos e sobre como a dimensão ambiental vem, dia a dia, ganhando espaço nesse contexto. Este artigo está estruturado em três partes: na primeira destacou-se o papel dos gestores de recursos humanos, na segunda foram apresentadas algumas evidências empíricas da atuação dos gestores de RH em contextos internacionais e, na ter-ceira, a questão da gestão ambiental como um novo desafio para os gestores de recursos humanos. A partir deste estudo concluiu-se que os gestores de RH precisam reconhecer e incorporar, nas práticas de recursos humanos, a dimensão ambiental, principalmente a partir do recrutamento, selecionando, treinando e recompensando as pessoas que apresentam atitudes e competências voltadas ao meio ambiente, o que contribuiria para uma gestão ambiental eficaz, inclusive resul-tando em melhorias nos resultados organizacionais.
Environmental management: a new challenge for human resources personnel?
Keywords: Human resource management; HR Managers; Environmental management; Integration; Challenge; Gestão de recursos humanos; Gestores de RH; Gestão ambiental; Integração; Desafio